2021
DOI: 10.21608/asejaiqjsae.2021.151650
|View full text |Cite
|
Sign up to set email alerts
|

Response of Canola Plant (brassica napus l.) To Reducing Nitrogen Fertilizer Rates by Adding Humic Substance

Abstract: Two field experiments were carried out at Itay El-Baroud Agricultural Research Station Farm-El Behira Governorate-Egypt during two successive winter seasons of 2016 /2017 and 2017/2018 to investigate the possibility of reducing nitrogen fertilizer rates by adding humic substance (Actosol ®) and their effects on growth, yield, yield components and some chemical properties of Serow 4 canola variety plants. The studied treatments consisted of seven different doses of recommended nitrogen (30 kg N / fed) with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The relative increase due to increasing N. levels from zero to 80 Kg N / fad., in number of pods / plant, 1000-seed weight (gm) and seed yield ton / fad., was about 11.74%, 30.49% and 69.87%, respectively. The obtained results are in agreement with reported by Keivanrad and Zandi (2012); Naderifa and Daneshian (2012); Aminpanah (2013); ; Farooq et al, (2017) Alam et al, (2018) and Mourad et al, (2021).…”
Section: -Seed Yield and It's Componentssupporting
confidence: 92%
See 1 more Smart Citation
“…The relative increase due to increasing N. levels from zero to 80 Kg N / fad., in number of pods / plant, 1000-seed weight (gm) and seed yield ton / fad., was about 11.74%, 30.49% and 69.87%, respectively. The obtained results are in agreement with reported by Keivanrad and Zandi (2012); Naderifa and Daneshian (2012); Aminpanah (2013); ; Farooq et al, (2017) Alam et al, (2018) and Mourad et al, (2021).…”
Section: -Seed Yield and It's Componentssupporting
confidence: 92%
“…These results are agreement with those reported by Keivanrad and Zandi (2014); Al-Solimani and Alghabzri (2015); Al-Solimani et al, (2015); Eman, El-Sarag andHassan (2016) andRiar et al, (2020). But, Mourad et al, (2021) found that nitrogen increase did not effect on oil content %, thus, insignificant Canola seed.…”
Section: -Seed Qualitymentioning
confidence: 89%